Design, synthesis and biological evaluation of anthranilamide derivatives as potent SMO inhibitors. Issue 6 (15th March 2020) - Ji, Dezhong; Zhang, Wanwan; Xu, Yungen; Zhang, Jing-Jing
Graphical abstract: Highlights: SMO inhibitors with novel structural features were developed by replacing the phthalazine core in LY2940680 with anthranilamide via a ring-opening strategy. The anthranilamide structure could mimic the phthalazine ring in LY2940680 by forming a pseudo-ring structure resulting from the intra-molecular hydrogen bond interaction between the oxygen atom of carbonyl group and hydrogen atom of the amino group. The pseudo-ring structure formed by anthranilamide and the hydrogen bond interaction between its carbonyl group and R400 of SMO, as evidenced by Glide docking study, suggested that the new compounds can mimic the binding conformation of LY2940680 to SMO. Difference in the inhibitory activity between the new compounds and LY2940680 were studied by molecular dynamic analysis. Abstract: A series of anthranilamide derivatives were designed and synthesized as novel smoothened (SMO) inhibitors based on the SMO inhibitor taladegib (LY2940680), which can also inhibit the SMO-D473H mutant, via a ring-opening strategy. The phthalazine core in LY2940680 was replaced with anthranilamide, which retained the inhibitory activity towards the hedgehog (Hh) signaling pathway as evidenced by a dual luciferase reporter gene assay. Compound 12a displayed the best inhibitory activity against the Hh signaling pathway with IC50 value of 34.09 nM, and exhibited better proliferation inhibitory activity towards the Daoy cell line (IC50 = 0.48 μM) than LY2940680 (IC50 = 0.79 μM).